Optics of an individual organic molecular mesowire waveguide: directional light emission and anomalous refractive index. (5th April 2016) - Tripathi, Ravi P N; Dasgupta, Arindam; Chikkaraddy, Rohit; Patra, Partha Pratim; Vasista, Adarsh B; Kumar, G V Pavan
Abstract: We report on experimental investigations performed on an isolated organic mesowire waveguide resting on a glass substrate. The waveguide was made of diaminoanthraquinone (DAAQ) molecular aggregates. First, we show directional emission of light from distal ends of the DAAQ waveguide. For a given mesowire geometry, operating in passive or photoluminescence regimes, we quantified the emission angles by combining multi-wavelength Fourier-plane optical microscopy and photoluminescence micro-spectroscopy. We found light emission in the photoluminescence regime to be more directional in nature compared to the passive waveguiding regime, which was supported by three-dimensional finite-difference time-domain (FDTD) simulations. Second, we measured the anomalous behaviour of refractive index as a function of emission wavelength using the spectra of directionally emitted light. Third, by using spatial-filtered collection optics, we observed and quantified single-excitation dual-channel directional, active emission from DAAQ mesowire. The results discussed herein has implication not only in understanding some fundamental aspects of exciton-polariton mediated directional light emission, but also in applications such as organic optical antennas and photonic couplers.